THE EFFECT OF COOPERATIVE LEARNING ASSISTED WITH MODULE AND STUDENTS LEARNING MOTIVATION TOWARD THE STUDY RESULT ON STUDENTS SENIOR HIGH SCHOOL - Hotman Sitanggang (Jurnal Pendidikan Fisika, 2014)
The aim of this research is to improve learning quality of high school students in grade ten (X) to the study material is about the vector. This research is a quasiexperimental study. Samples selection is random, using the control class from the adjacent class to avoid the large bias. The results of samples selection are the students of class X-H as the control class and the students of class X-I as the experimental class. The motivation variable was distinguished from the observations of student activities at the pre-study and at current research. Highly motivated students are the students who actively ask the questions and give answers to problems. While the low-motivated students are the students whose learning activities are the less. This research was designed using 2x2 factorial ANOVA, namely the effects of cooperative learning between learning without module and module-assisted learning on students’ learning results; and the effects of students’ learning motivation between highly motivated students and low motivated students. After given the treatment, those are: the same pre-test, cooperative learning without modules in control class, module-assisted cooperative learning in experimental class, the same post-test, questionnaires distribution, collection and tabulation of the data. The data were analyzed using qualitative-descriptive technique and percentage. The data analysis results using SPSS 17.0 conclude that: (1) There is a significant difference of study results in cooperative learning without module against module-assisted cooperative learning. (2) There is a significant difference of study results between highly motivated students and low motivated students. (3) There is a significant difference of study results between the group of cooperative learning and the group of student motivation at the significance value of = 0.05.